REVIEWING THE POTENTIAL BENEFITS OF PORN VIDEOS IN THE CONTEXT OF SEXUAL HEALTH. - Taufiq Arsyad; Ami Kasai (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2024)
This study aimed to explore the potential benefits of pornographic videos in the context of sexual health based on a comprehensive review of the literature. Findings revealed that pornographic videos can play a role in informal sexual education, sexual therapy, safe exploration of sexual fantasies, as well as improving sexual well-being and communication in intimate relationships. However, these benefits can only be obtained if porn videos are consumed in a moderate, responsible manner and in accordance with proper ethical guidelines. The study also emphasizes the importance of considering factors such as consumption patterns, type of porn content, and individual characteristics in determining whether porn videos have a positive or negative impact on sexual health. In addition, this study suggests the development of comprehensive guidelines and regulations regarding the use of pornographic videos in the context of sexual health, as well as further in-depth and holistic research to understand the complexity of the relationship between pornographic videos and sexual health more comprehensively.